Calf muscle pump tensing as a novel maneuver to improve the diagnostic performance of detecting patent foramen ovale during transesophageal echocardiography - Zhu, Jianbo; Chen, Anni; Zhu, Lei; Li, Yun; Tang, Yunyi; Huang, Yanhua; Shen, Hualiang; Jiang, Zhenzhen; Liu, Xiatian (Frontiers in Neurology, 2023)
Objective The Valsalva maneuver is the most sensitive provocative maneuver for patent foramen ovale detection. However, nearly half of patients are unable to perform the Valsalva maneuver well. The aim of this study was to investigate the mechanism of action of calf muscle pump tensing (TENSE) as a novel patent foramen ovale (PFO) provocative maneuver and to evaluate the diagnostic value for PFO and the effect on right-to-left shunt volume compared with the Valsalva maneuver. Methods This study prospectively investigated 171 patients who were highly suspected to have PFO clinically. Five patients with atrial septal defects newly diagnosed on transesophageal echocardiography (TEE) were excluded. 166 patients were injected with agitated saline under three provocative maneuvers: Valsalva maneuver, TENSE, and Valsalva + TENSE combined maneuver. The patients were divided into the effective Valsalva group (n = 93) and ineffective Valsalva group (n = 73) according to whether they could perform an effective Valsalva maneuver. TENSE consisted of the straightening of both lower limbs, and when the right atrium was filled with microbubbles, the patient performed instantaneous ankle dorsiflexion movements while maintaining dorsiflexion for 3–5 s. Results Overall, the PFO detection rate of the Valsalva + TENSE combined maneuver (78 [50.1%]) was significantly higher than that of the Valsalva maneuver (51 [30.7%]) and TENSE maneuver (57 [34.3%]) (P < 0.001). In the patients who were able to perform an effective Valsalva maneuver, the PFO detection rate by TENSE was not significantly different from that by the Valsalva maneuver (Valsalva 37/93 [39.8%] vs. TENSE 31/93 [33.3%], P > 0.05), while for the patients who performed an ineffective Valsalva maneuver, the PFO detection rate by the TENSE maneuver was higher than that by the Valsalva maneuver (TENSE 26/73 [35.6%] vs. Valsalva14/73[19.2%], P = 0.017). Conclusion TENSE is a simple and effective provocative maneuver in the diagnosis of PFO using TEE and can assist the Valsalva maneuver. For patients who cannot perform an effective Valsalva maneuver, TENSE can be an alternative to the Valsalva maneuver to some extent.